2015
DOI: 10.4314/tjpr.v14i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1-Substituted-4-(Pyridin-4-yl) [1,2,4] Triazolo [4,3-a] Quinazolin-5(4H)-ones as a New Class of H1- Antihistaminic Agents

Abstract: Purpose: To synthesize a new series of 1-substituted-4-(pyridin-4-yl) [1,2,4] triazolo [4,3-a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The data of computer prediction of the biological activity obtained are fully consistent with the fact that [1,2,4]triazolo[4,3-a]quinazolin-5(4H)-one derivatives are similar in their chemical structure to the chemical structures described as promising nonsedative H1-antihistaminic drugs [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The data of computer prediction of the biological activity obtained are fully consistent with the fact that [1,2,4]triazolo[4,3-a]quinazolin-5(4H)-one derivatives are similar in their chemical structure to the chemical structures described as promising nonsedative H1-antihistaminic drugs [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Resultssupporting
confidence: 74%
“…Derivatives of [1,2,4] triazolo [4,3-a]quinazolin-5(4H)-one, which are representatives of the important class of condensed heterocycles possessing a wide range of the biological activity, attract particular interest in this direction. Among their potential pharmacologically significant properties the H1-antihistaminic [1][2][3][4][5][6][7][8][9][10][11], anticonvulsant [12], antibacterial [13][14][15], antitubercular [13,15], antifungal [13,14], anticancer [15], anti-asthmatic [10,16], antiHIV [13], anti-allergic [16], anti-inflammatory [16,17] bioactivities should be mentioned. It determines the prospects for developing synthetic approaches to fundamentally new compounds of the specified class.…”
mentioning
confidence: 99%
“…The 1 H NMR spectra of 26 revealed the characteristic methylene proton at δ 4.34 (CH 2 ). Also, the literature indicated that methyl dithiocarbamate group in compound 3 reacts with anthranilic acid or methyl anthrnilate, leading to the formation of quinazoline and its derivatives [19][20][21][22][23]. Thus, interaction of 3 with anthranilic acid in refluxing ethanol in the presence of TEA as catalyst to yield the thiourea intermediate 27 which underwent cyclization via loss of water molecule yielding quinazoline derivative 28, Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…As important and useful fused heterocycles, N 3-substituted and N 1, N 3-disubstituted 2,3-dihydroquinazolin-4­(1 H )-ones have drawn much attention due to their broad range of pharmacological and biological properties, such as anticancer, antidiabetic, antihypertensive, anti-inflammatory, , antibacterial, antihistaminic, antiviral, antitumor, diuretic, , vasodilatory, , antiobesity, , antimalarial, anthelmintic, anti-Shiga toxin, antiricin, antimicrobial, , and anticonvulsant activities. In addition, N 3-substituted 2,3-dihydroquinazolin-4­(1 H )-ones can also be readily oxidized to the corresponding quinazolin-4­(3 H )-one derivatives, which are important building blocks in natural products and synthetic drugs .…”
mentioning
confidence: 99%